(3cJGH GdbfGYI aj GdaYd GdeYJd EPG EJUd Hg hGh GdLeGYIs - (3jhSa Hf ESeGYjd GdUaJjs ((3GdcJHNGfI GdNOjhjI (B_ (3eUQ s)
(3ChdgG (B:s
(3GdMeO ddg GdPi JfRg Yf GdCZQGV ai GdCaYGd hGdCMcGe CeG HYO ajbhd jhSa Hf CSeGYjd SYjO GdUaJi GdeGdci bO cfJ CSeY cKjQkG ef GdfGS jdMf ai bhdg Udi Gddg Ydjg hSde JgGOhG JMGHhG ajbQDfg HVe GdOGd s
(3BNQgG (B:s
(3hMPagG ai GdKGfi Khdg QRbJ GdYde Ci QRbc Gddg GdYde GdfGaY GdehUd Edi Gddg JYGdi hGdMeO ddg GdPi gOGfG dgPG heG cfG dfgJOi dhdG Cf gOGfG Gddg hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdfMhs